Impact of Positive Thoughts on Immunity - Preethi Shankar1 , Dinesh Premavathy2 , Preetha S (Institute of Medico-legal Publications Pvt Ltd, 2020)
Immunity plays a major role, by protecting us from various foreign antigens.It is broadly classified intotwo major groups, active immunity and passive immunity. Foods such as citrus fruits, broccoli, garlic,ginger, yogurt, and almonds are immune boosting foods.The positive thoughts also have a good impactover diseases like diabetes and cancer and it can be overcome by the positive thoughts. Positive thoughtsare directly proportional to the positive effects on immunity.The positive thoughts are directly proportionalto the positive effects on immunity by controlling or decreasing stress level. The decrease in the positivethoughts have direct impact on health, thus it paves a way for occurrence of disease. The aim of the presentstudy is to assess the knowledge of positive thoughts on immunity among the general population. An onlinebased survey was conducted among 100 people on the impact of positive thoughts on immunity. The resultswere analyzed and represented as graphs. The present study thus concluded that based on the survey peoplehad less knowledge about the impact of positive thoughts on immunity.